Resist‐ and Etching‐Free Patterning Mediated by Predefined Photosensitive Polyimide for Two‐Dimensional Semiconductor‐Based Photodetectors. Issue 5 (15th January 2021) - Lim, Yi Rang; Park, Hyunjin; Bae, Garam; Seo, Min Ki; Yun, Hye‐Won; Yoo, Sungmi; Myung, Sung; Lim, Jongsun; Lee, Sun Sook; An, Ki‐Seok; Won, Jong Chan; Song, Wooseok; et al.
Abstract: Even though molybdenum disulfide (MoS2 ) possesses superb features, its practical application in optoelectronics is hindered by the lack of a reliable synthetic route for producing large‐scale two‐dimensional (2D) MoS2 with spatial homogeneity and a pertinent patterning technique that can be used to realize 2D MoS2 ‐based photodetector arrays. To resolve these issues, the effectiveness of an unprecedented combination of a solution‐based synthetic route with resist‐ and etching‐free patterning of 2D MoS2 mediated by pre‐defined photosensitive polyimide (PSPI) for realizing 2D MoS2 ‐based photodetector arrays is demonstrated. A solution‐based large‐area compatible approach is adopted for the synthesis of MoS2 . Comprehensive structural and chemical analysis of the MoS2 synthesized by altering the concentration of ammonium tetrathiomolybdate is performed to determine the optimum conditions for enhancing the photoelectrical responses of MoS2 ‐based photodetectors. It is ascertained that the photocurrent of MoS2 ‐based photodetectors fabricated by PSPI‐assisted patterning is unequivocally greater than that of photodetectors produced via the conventional photolithography process owing to the absence of photoresist residues associated with impeding photon absorption and providing scattering centers of photogenerated carriers. Abstract : A solution‐based synthetic route with resist‐ and etching‐free patterning of two‐dimensional (2D) molybdenum disulfide (MoS2 ) mediated by predefined photosensitive polyimide (PSPI) for realizing 2D MoS2 ‐based photodetector arrays is combined. The photocurrent of MoS2 ‐based photodetectors fabricated by PSPI‐assisted patterning is unequivocally greater than that of photodetectors produced via the conventional photolithography process owing to the absence of photoresist residues.